Etching and heating treatment combined approach for superhydrophobic surface on brass substrates and the consequent corrosion resistance. (January 2016) - Jie, Han; Xu, Qunjie; Wei, Liu; Min, YuLin
Highlights: The superhydrophobic surfaces on brass substrates were prepared by etching and heat treatment combination approach. The achieved superhydrophobic surface has a contact angle as high as 153.6°. The superhydrophobic surface exhibited excellent and persistent corrosion resistance in 3.5 wt% NaCl aqueous solution. Abstract: Designing micro-nano structure is one of promising method to fabricate hydrophobic surfaces. In this paper, we demonstrated a combining etching and heat treatment approach to achieve a superhydrophobic surface on brass. Following by simple modification using stearic acid, the water contact angle on micro-nano structured brass was 153.6°, along which exhibited good and persistent corrosion resistance in 3.5 wt% NaCl aqueous solutions. This method could provide an effective route to fabricate superhydrophobic surface with corrosion resistance and self-cleaning properties for applications in the metal alloys materials.